2011
DOI: 10.1007/s11802-012-1844-7
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of phosphate-solubilizing bacteria from seagrass rhizosphere soil

Abstract: Phosphate-solubilizing bacterial strains (6 Nos.) were isolated from the rhizosphere soils of two seagrasses (Halophila ovalis (R. Br.) Hook and Halodule pinifolia (Miki) Hartog) in the Vellar estuary. Experimental studies found that the strain PSSG6 was effective in phosphate solubilization with Phosphate Solubilization efficiency index E = 375 ± 8.54, followed by the strain PSSG5 with Phosphate Solubilization efficiency index E = 275 ± 27.3. Of the 6 strains isolated, the strains PSSG4 and PSSG5 belonged to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 33 publications
2
8
0
1
Order By: Relevance
“…Results showed that among these four potent isolates, the RK24 strain was the most efficient phosphate solubilizer on PVK medium with SI 4.66 and PSE 366.6. These results are interesting in comparison with results found by Qureshi et al (2012) and Ghosh et al (2012). Modified Pikovskaya's agar containing bromophenol blue as indicator was used, which can improve the clarity and visibility of the yellow-colored halo around colonies.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Results showed that among these four potent isolates, the RK24 strain was the most efficient phosphate solubilizer on PVK medium with SI 4.66 and PSE 366.6. These results are interesting in comparison with results found by Qureshi et al (2012) and Ghosh et al (2012). Modified Pikovskaya's agar containing bromophenol blue as indicator was used, which can improve the clarity and visibility of the yellow-colored halo around colonies.…”
Section: Discussionsupporting
confidence: 80%
“…Thus, intensive screening of phosphate solubilizing bacteria with genetic potential for increased resistance to extreme salt, pH and temperature in arid and semi-arid area, can help to choose the best bacteria for use in production of biological fertilizers (Mehta et al 2001;Ramani 2011). Several studies have reported the isolation of phosphate solubilizing bacteria from rhizospheric soil (Barea et al 1976;Prasanna et al 2011;Ghosh et al 2012;Ambrosini et al 2012). In the present study, cabbage rhizosphere was selected for isolation of phosphate solubilizing bacteria.…”
Section: Discussionmentioning
confidence: 97%
“…PSMs able to release phosphorus from the soil minerals play a key role in soil fertility (Wakelin et al 2012) when P availability is low or P demand is high. Most relevant literature pertains to PSB and their potential use for the enhancement of soil fertility (Collavino et al 2010; Ghosh et al 2012). However, a few filamentous nonmycorrhizal fungi are also involved in phosphate solubilization, especially Aspergillus spp.…”
Section: Discussionmentioning
confidence: 99%
“…This could be the first report of such Klebsiella spp., although previous reports described some Klebsiella spp. as phosphate solubilizers (Ghosh et al, 2012;Islama et al, 2007;Chung et al, 2005).…”
Section: Discussionmentioning
confidence: 99%